2016
DOI: 10.1016/j.chiabu.2015.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Multimethod prediction of physical parent–child aggression risk in expectant mothers and fathers with Social Information Processing theory

Abstract: The Social Information Processing (SIP) model postulates that parents undergo a series of stages in implementing physical discipline that can escalate into physical child abuse. The current study utilized a multimethod approach to investigate whether SIP factors can predict risk of parent-child aggression (PCA) in a diverse sample of expectant mothers and fathers. SIP factors of PCA attitudes, negative child attributions, reactivity, and empathy were considered as potential predictors of PCA risk; additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 72 publications
(95 reference statements)
2
34
0
2
Order By: Relevance
“…However, low couple satisfaction and low social support may be more problematic for mothers’, rather than fathers’, PCA risk (Schaeffer et al 2005; Price-Wolff 2015). Others have reported that higher abuse risk fathers report less empathic perspective-taking ability—a finding not mirrored in mothers (Perez-Albeniz and De Paul 2004)–whereas empathy was less apparent as a risk factor in a model of PCA risk in fathers (Rodriguez et al 2016). Nonetheless, relatively few direct comparisons of comprehensive abuse risk models have been performed between mothers and fathers.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…However, low couple satisfaction and low social support may be more problematic for mothers’, rather than fathers’, PCA risk (Schaeffer et al 2005; Price-Wolff 2015). Others have reported that higher abuse risk fathers report less empathic perspective-taking ability—a finding not mirrored in mothers (Perez-Albeniz and De Paul 2004)–whereas empathy was less apparent as a risk factor in a model of PCA risk in fathers (Rodriguez et al 2016). Nonetheless, relatively few direct comparisons of comprehensive abuse risk models have been performed between mothers and fathers.…”
Section: Introductionmentioning
confidence: 95%
“…Fathers are implicated in approximately half of those engaging in physical maltreatment (Sedlak et al 2010). Current evidence implies fathers demonstrate comparable risk profiles to mothers, with modest differences (e.g., Rodriguez et al 2016; Schaeffer et al 2005; Smith Slep and O’Leary 2007). However, low couple satisfaction and low social support may be more problematic for mothers’, rather than fathers’, PCA risk (Schaeffer et al 2005; Price-Wolff 2015).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations